2016
DOI: 10.1101/051300
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic exploration of unsupervised methods for mapping behavior

Abstract: To fully understand the mechanisms giving rise to behavior, we need to be able to precisely measure it. When coupled with large behavioral data sets, unsupervised clustering methods offer the potential of unbiased mapping of behavioral spaces. However, unsupervised techniques to map behavioral spaces are in their infancy, and there have been few systematic considerations of all the methodological options. We compared the performance of seven distinct mapping methods in clustering a data set consisting of the x… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Individual measures of fly behavior (Ayroles et al, 2015;Bierbach et al, 2017;Buchanan et al, 2015;Freund et al, 2013;Kain et al, 2012;Linneweber et al, 2019;Schuett et al, 2011;Todd et al, 2017;Werkhoven et al, 2019a) are typically stable over days. This was indeed the case for the specific turn biases that flies showed in the dark and light conditions, as well as their individual LDM values ( Fig 1I).…”
Section: Resultsmentioning
confidence: 99%
“…Individual measures of fly behavior (Ayroles et al, 2015;Bierbach et al, 2017;Buchanan et al, 2015;Freund et al, 2013;Kain et al, 2012;Linneweber et al, 2019;Schuett et al, 2011;Todd et al, 2017;Werkhoven et al, 2019a) are typically stable over days. This was indeed the case for the specific turn biases that flies showed in the dark and light conditions, as well as their individual LDM values ( Fig 1I).…”
Section: Resultsmentioning
confidence: 99%
“…We did not assess the day-to-day persistence of behavioral modes identified in the unsupervised analysis, so the observed variation across flies could reflect moods rather than permanent personalities. However, previous supervised (Kain et al, 2013) and unsupervised (Todd et al, 2017) analyses of spontaneous microbehaviors similar to those identified by unsupervised approaches have found such behaviors to persist across days.…”
Section: Discussionmentioning
confidence: 87%
“…Genetic model systems hold particular promise for the mechanistic dissection of this variation, and intragenotypic variability (IGV) in behavior has been characterized in mice (Freund et al, 2013), zebrafish (Pantoja et al, 2016) and Drosophila. In flies, IGV of many behaviors has been studied, including: phototaxis (Kain et al, 2012), locomotor handedness and wing-folding , spontaneous microbehaviors (Kain et al, 2013;Todd et al, 2017), thermal preference and objectfixated locomotion (Liu et al, 2018). Mechanistic studies of these behavioral phenomena have addressed two major questions: 1) what biological mechanisms underlie the magnitude of behavioral variability (e.g., genetic variation (Ayroles et al, 2015), or neural state variation (Kain et al, 2012;), and 2) what specific differences within individual nervous systems predict individual behavioral biases (Liu et al, 2018;Mellert et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Converting postures (e.g., ‘straight forearm’ or ‘extended elbow’) into actions (e.g., ‘reaching’) requires some way of clustering together stereotyped sequences of postures that are repeatedly seen with only minor variations. Methods to accomplish this range from embedding postures into a low-dimensional space to find ‘clumps’ of similar sequences[18] to identifying when one posture is predictable from previous postures[19], though other methods exist[15,17,20,21]. What is exciting about these ‘unsupervised’ algorithms is that they offer not only ever-more-precise quantification of what an animal is doing at each moment in time, but also reveal the underlying structure of behavior (e.g., which behaviors are sub-programs of other behaviors or which behaviors co-occur), and offer the potential for discovering completely new behaviors.…”
Section: Automated Methods To Quantify Behaviormentioning
confidence: 99%